Enostosis-Like Lesion in Thoroughbred Horse - Siqueira Raimundo, Bruna Patrícia; Martins de Oliveira Veiga, Carlos Eduardo; De Bastiani, Grasiela; Jacobsen, Tainã Kuwer (Acta Scientiae Veterinariae, 2022)
Background: Enostosis like lesions are characterized by areas of intramedullary sclerosis affecting the long bones and their presence in any cases may be not associated with lameness. It has a migratory characteristic and, therefore there is the occurrence of lameness at different sites from the initial lesion. Its etiology is speculative and has been attributed to intraosseous increased pressure, of Havers’ canals compression, stimulation of unmyelinated fibers and circulating platelet aggregates. Diagnosis is made through nuclear scintigraphy and associated with radiographic examination. This paper aims to report a clinical case on the use of scintigraphy for the reference diagnosis of enostosis-type injury and treatment through surgical bone decompression. Case: A 2-year-old thoroughbred mare, weighing 483 kg, with a history of acute lameness of the left pelvic limb associated with the no previous signs of trauma and no noteworthy changes in radiographic and ultrasound images, was referred to the Horse Center Veterinary Clinic. In the examination of the locomotor system, the animal presented a 2/5 degree lameness in a straight line, with accentuated exacerbation of the same after flexion of the left femoro-tibio-patellar joint. In addition, presented a reduction in the caudal phase of the stride and croup asymmetry associated with mild myopenia. The findings of the scintigraphic exam characterized by intense focal area of hyperconcentration of medullary radiopharmaceutical in the proximal third of the right third metatarsal, and multiple areas of hyperconcentration in the aspect proximal to the distal third of the left tibia. In the radiographic images, multifocal radiopaque regions that coincided with the areas of radiopharmaceutical hyperconcentration were observed. The initial treatment was based on rest, use of non-steroidal antiinflammatory drugs and acetylsalicylic acid. In the 60 days’ later evaluation of the first exam, the patient returned to the clinic presenting 4/5 degree lameness and with an unsatisfactory evolution. Therefore, surgical bone decompression was performed on the left radius through intramedullary perforations with a 3.5 mm drill in the lesion sites. Approximately 30 days after the surgical procedure, the animal returned to the clinic complaining of acute 2/5 degree lameness of the left pelvic limb. The patient was removed from his race career and destined for amateur jumping events where he is currently doing the same without presenting a clinical complaint of persistent lameness. Discussion: The presence of focal areas of radiopharmaceutical hyperconcentration in several bones of a limb, not just in the same lame limb, makes it even more difficult to understand this pathology. The intensity of radiopharmaceutical uptake evident in scintigraphy exams is related to the degree of lameness. Severe lameness is associated with intense radiopharmaceutical concentration indicating an acute stage of the disease, as well as a decrease in radiopharmaceutical concentration in follow-up exams, demonstrating an improvement in the degree of lameness. In the present clinical case described, there was a decrease in the radiopharmaceutical concentration in the right radius, but in the left radius, the limb in which spinal cord decompression was performed, it was still possible to observe radiopharmaceutical hyperconcentration. This was possibly due to an inflammatory bone process caused by surgical decompression. The literature suggests a favorable prognosis for the return to athletic function, with clinical resolution after following a period of rest and administration of non-steroidal anti-inflammatory drugs. The patient in the described clinical case returned to sports activities with a reduced athletic performance requirement, replacing running events with basic and amateur jumping events. Keywords: lameness, intramedullary sclerosis, bone, equine. Título: Enostose múltipla em equino puro sangue de corrida Descritores: claudicação, esclerose intramedular, osso, equino.